Massive Chondrolysis and Joint Destruction after Artificial Anterior Cruciate Ligament Repair - Jack Carlson; Olivia Fox; Peter Kilby (Case Reports in Orthopedics)
The Ligament Augmentation Reconstruction System (LARS) is an artificial ligament made of polyethylene terephthalate (PET) used for anterior cruciate ligament (ACL) reconstruction in Australia. Poor results with previous generations of synthetic grafts causing synovitis, graft failure, and premature osteoarthritis have encouraged the production of the newer LARS ligament with good results. We present a case of massive chondrolysis and joint destruction after LARS implantation requiring total knee replacement in a 23-year-old male. This case documents a rare and severe complication to the LARS ligament as caution for the implementation of this device in young athlete.